EDUKASI KESEHATAN METODE DIDAKTIK DAN MEDIA POSTER MENINGKATKAN PENGETAHUAN TENTANG PENCEGAHAN HIPERTENSI - Panganton, Enjelita; Sepang, Mareyke; Oroh, Cindi (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2022)
Introduction: Hypertension is a non-communicable disease that contributes to the highest number of causes of death in the world. People with hypertension are at risk of experiencing disturbances in several body functions such as the heart, blood vessels, brain, and so on. Therefore, it is important to make efforts to prevent hypertension or complications with health education. The education provided can use the diactive method supplemented by poster media, that can provides an attraction for participants to understand the education delivered. Objective: To determine the effect of health education given using the didactic method and media posters on the level of knowledge in preventing hypertension. Methods: This study used the pre-experimental method with a one group pre and post-test design without a control group. The population is all the people of Gamhoku Village aged from 18-70 years, totaling 440 people. Sampling using purposive sampling method, with the formula Arikunto obtained a total sample of 110 people. The instruments used were knowledge questionnaires and media posters. Providing education which was given once, while the poster media was left to the respondents. Knowledge level measurements were carried out before education, and 3 days after education was given. Results: Data analysis using the Wilcoxon Sign Rank Test found p-value = 0.000 <0.05. Conclusion: There is a significant influence in the provision of health education using the didactic method and media posters, on the level of knowledge in preventing hypertension in Gamhoku Village, Tobelo Selatan District.